Impact of free trade agreements and anti-dumping on Malaysian trade flows - Said, Rashidi (2018)
The issues of the proliferation of free trade agreements (FTAs) and the widespread use of anti-dumping actions in international trading system have attracted much interest among policymakers and scholars to study the impacts of these trade policy instruments to trade. Therefore, the general objective of this research is to examine the impacts of FTA liberalisation and anti-dumping actions on international trade flows, particularly on the extensive and intensive margins of trade between Malaysian and its trading partners. This research utilises the United Nations Commodity Trade (COMTRADE) data from 1994 to 2014. The margins are constructed using Hummels and Klenow (2005) method, with empirical analysis is based on the gravity model framework. The number of FTAs has increased rapidly since 1990s. As for Malaysia, it has signed twelve FTAs by end-2014. The first specific objective of this research is to evaluate the impacts of Malaysian FTAs on extensive and intensive margins. The research constructs trade margins using the imports data among 48 countries in the Malaysian FTA network. The research finds positive impact of most FTAs on intensive margin when FTAs enter into force with majority of them is regional FTAs. The evidence shows a shift in trade patterns i.e. 4.0 per cent reduction in extensive margin from bilateral FTAs to 41.6 per cent increase in intensive margin from regional FTAs. These results show that much of the increase in trade is evidenced by the trade in existing products.The reductions in trade barriers from liberalisation policy have resulted in— fairly or unfairly—massive flows of imports, which triggered the increased use of anti-dumping actions around the world. The second specific objective of this research is to investigate the impacts of anti-dumping actions imposed by 14 Malaysian FTA members against their 48 trading partners on extensive and intensive margins. Utilising anti-dumping information from 1994 to 2014 in Bown (2016), the gravity model estimate finds that the anti-dumping actions significantly impacted intensive margin. The anti-dumping actions caused reduction in intensive margin by 2.5 per cent a year following the imposition but only significantly reduced intensive margin by 6.3 per cent in the second year and 7.7 per cent in the third year. For WTOijt+ dummy variable, positive WTOijt+ coefficients indicate that a stricter anti-dumping discipline in FTAs has helped FTA members to increase both trade margins. Malaysia as one the major trading nations has been exporting a few major products such as iron and steel, chemicals, textiles, and machinery to the FTA partners. The impositions of anti-dumping actions against these products can impact both margins. The third objective of this research examines the impacts of 158 anti-dumping actions filed by eleven Malaysian FTA partners from 1994 to 2014 on extensive and intensive margins in sectors of Malaysian export interests. The gravity model estimates significant and stronger impacts of antidumping actions on intensive margin when the sectors of base metal and machinery are covered in Malaysian imports. The results help to explain how an anti-dumping action can have a stronger impact on trade margins when a wider range of products is covered by the actions. The findings of this research bring some policy implications to policymakers on impacts of FTAs and anti-dumping policies to trade. The positive impact of regional FTAs on intensive margin shows a significant role of these FTAs can play in spurring improvements in trade in existing products. While FTAs promote trade, the excessive use of anti-dumping actions for protection can have some negative impacts. Therefore, it is important for policymakers to be more cautious in utilising the measures, while maintaining their legitimate rights as provided under the WTO rules.